COMPARATIVE TRANSCRIPTOMIC ANALYSIS IDENTIFIES EPITHELIAL-MESENCHYMAL TRANSITION AND INFLAMMATION AS COMMON PATHOGENETIC MECHANISMS IN HYPERTENSIVE AND DIABETIC NEPHROPATHY. (June 2022) - Nordb⊘, Ole Petter; Landolt, Lea; Eikrem, Øystein; Scherer, Andreas; Leh, Sabine; Palmer, Jessica Furriol; Apeland, Terje; Mydel, Piotr; Marti, Hans-Peter
Abstract : Objective: Type 2 diabetic (T2DN) and hypertensive nephrosclerosis (HN) are the main causes of chronic kidney disease (CKD). To obtain novel insights into pathogenetic mechanisms, potentially suggesting common therapeutic procedures, we comparatively nalysed transcriptomes of kidney biopsies obtained from patients with T2DN or HN and control archived formalin-fixed and paraffin-embedded (FFPE) kidney biopsies. Design and method: FFPE kidney biopsies from adult patients were selected from the Norwegian Kidney Biopsy Registry. Specimens from patients with HN, T2DN and normal-appearing control renal biopsies (Ctrl) (n = 6 for each group) were assessed. Total RNA was extracted from 10 μm whole kidney sections and processed for RNA sequencing, while immunohistochemistry (IHC) was performed on 3-μm tissue sections. Enzyme-Linked ImmunoSorbent Assay (ELISA) targeting the AXL receptor tyrosine kinase was performed on serum from separate cohorts with HN and T2DN/T1DN. Results: Gene expression analysis showed 769 differentially expressed genes (DEG) for T2DN and 284 HN genes (log fold change > 1, adjusted P < 0.05). Only 39 of the HN genes were uniquely DEG compared to T2DN. Cluster analysis on the RNA seq data separated diseased and normal tissues, also with a distinct overlap between HN and T2DN profiles. Detailed analysis of gene expression profiles revealed upregulation of pathways related to partial epithelial to mesenchymal transition, including extracellular matrix organisation in both diseases. AXL and vimentin expression was also enhanced at the protein level in both HN and T2DN biopsies, as detected by immunohistochemistry (IHC). AXL abundance was also increased in serum from T2DN/T1DN and HN patients. Pathways related to inflammation was also overexpressed, particularly related to TH1 and TH2 helper cell pathways. The presence of CD4 and CD8 positive T- cells were confirmed by IHC. Conclusions: Similarities of T2DN and HN proteomes suggest common pathogenetic mechanisms and the possibility to envisage targeted treatments addressing both main causes of CKD.